2017
DOI: 10.1186/s12967-017-1354-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-strain probiotic supplement for 12 weeks in circulating endotoxin levels and cardiometabolic profiles of medication naïve T2DM patients: a randomized clinical trial

Abstract: BackgroundThe present randomized clinical trial characterized the beneficial effects of a multi-strain probiotics supplementation on improving circulating endotoxin levels (primary endpoint) and other cardiometabolic biomarkers (secondary endpoint) in patients with T2DM.MethodsA total of 78 adult Saudi T2DM patients (naïve and without co-morbidities) participated in this clinical trial and were randomized to receive twice daily placebo or probiotics [(2.5 × 109 cfu/g) containing the following bacterial strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 27 publications
6
63
0
5
Order By: Relevance
“…Interestingly, our data showed that the relative abundance of the family Bifidobacteriaceae and Bifidobacterium bifidum was higher in the MCA group than the HFD group. Previous studies showed that the probiotics containing Bifidobacterium bifidum plays important role to prevent and treat patients with obesity and insulin resistance [45,46]. Our data showed that MCA treatment increase Bifidobacterium bifidum in HFD-fed mice ( Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, our data showed that the relative abundance of the family Bifidobacteriaceae and Bifidobacterium bifidum was higher in the MCA group than the HFD group. Previous studies showed that the probiotics containing Bifidobacterium bifidum plays important role to prevent and treat patients with obesity and insulin resistance [45,46]. Our data showed that MCA treatment increase Bifidobacterium bifidum in HFD-fed mice ( Fig.…”
Section: Discussionsupporting
confidence: 56%
“…However, the association between probiotic treatment and diabetes is less clear with a small number of studies showing no such association . For example, in a recent clinical trial, type 2 diabetic patients receiving a consortium of eight different probiotic strains exhibited significantly higher median glucose levels, in addition to higher circulating TC and LDL‐C …”
Section: Probiotics Hypertension and Hyperglycemiamentioning
confidence: 99%
“…Only a non-significant increase in HDL-C level was observed in the experimental subjects [62]. Similarly, 12 weeks of the randomized controlled clinical study suggested that the Ecologic ® Barrier supplementation did not improve the lipid profile in T2D patients [63].…”
Section: Effect Of Probiotics Supplementation On Lipid Profile: Non-smentioning
confidence: 99%
“…Studies based on the intervention of multi-genus, multi-species, multi-strain (strains of same species) probiotic preparation has been reported with positive effect on lipid profile [24][25][26]28,[31][32][33][34][36][37][38][39]47,48], while several studies reported no effect of multi-genus and multi-species probiotic intervention on the lipid profile [55][56][57][58][59][60][61][62][63]. Even though intervention of Ecologic ® Barrier (B. bifidum W23, B. lactis W51, B. lactis W52, L. acidophilus W37, L. brevis W63, L. casei W56, L. salivarius W24, Lactococcus lactis W19 and W58) exhibit hypocholesterolemic effect on different subjects (individuals with T2D [38]; obese postmenopausal women [39]) with different intervention duration (six months [38]; 12 weeks [39]), dosage of probiotic mixture does not influence the cholesterol-lowering ability of the probiotic mixture.…”
Section: Opinion On the Hypocholesterolemic Effect Of Reviewed Probiomentioning
confidence: 99%